1990
DOI: 10.1007/bf01973374
|View full text |Cite
|
Sign up to set email alerts
|

Tissue accumulation of lipoprotein associated toxaphene in normo- and hypolipidemic mice

Abstract: Normo- and hypolipidemic mice were given a single i.v. injection of 14C-toxaphene associated with low density lipoprotein (LDL), high density lipoprotein (HDL) or dimethyl sulfoxide (DMSO). The tissue distribution of radioactivity was studied 20 min and 4 h after the application. In the normolipidemic mice at 20 min postinjection there was high uptake of the 14C-toxaphene preparations in the liver and adrenals followed after 4 h by a redistribution to the adipose tissues. In the hypolipidemic mice, proportiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Fingerling et al. (14) state that toxaphene consists of at least [180][181][182][183][184][185][186][187][188][189][190] components mostly with the formula C 10 H 18-n Cl n or C 10 H 16-n Cl n where n is 6-10. Buser et al (15) report that polychlorobornanes (C 10 H 18-n Cl n where n = 5-12) are formed as the main components in a Wagner-Meerwin type rearrangement reaction.…”
Section: Physical and Chemical Propertiesmentioning
confidence: 99%
“…Fingerling et al. (14) state that toxaphene consists of at least [180][181][182][183][184][185][186][187][188][189][190] components mostly with the formula C 10 H 18-n Cl n or C 10 H 16-n Cl n where n is 6-10. Buser et al (15) report that polychlorobornanes (C 10 H 18-n Cl n where n = 5-12) are formed as the main components in a Wagner-Meerwin type rearrangement reaction.…”
Section: Physical and Chemical Propertiesmentioning
confidence: 99%
“…Mohammed and co-workers initially found irds, and less 14C-radiolabeled toxaphene in the liver Idition, and adrenals and more in the kidney and utagenic heart of hypolipidemic mice (181 (184) showed that in addition to inducing cytochrome P450 and aniline hydroxylase activity in the liver, toxaphene also induces activity of these enzymes in the kidney. (1).…”
Section: Toxicokindtcs and Biotansforimentioning
confidence: 99%